Design and control of parallel three-Phase T-type three-level inverter - Qiu, Lihan (Nanyang Technological University, 2024)
With the growth of renewable energy generation such as photovoltaic and wind power, the power required by key equipment inverters is increasing. However, the power rating of individual inverter is limited by semiconductor switching devices. In order to increase the current capacity and reduce the cost of inverter system for high power application, the parallel technique is of significant research value. Meanwhile, compared with the traditional two-level inverter, the three-level inverter has the advantages of high efficiency and small size of passive components. Especially, the T-type three-level inverter is a widely used topology in the low and medium voltage field because of its small number of power devices, balanced loss distribution and low cost. The aim of this project is to study the parallel techniques of T-type three-level inverter, including interleaving modulation and inverter modular parallel, to develop the simulation model of parallel three-phase T-type three-level inverter, and to realize the grid-connected control, current and voltage balance control. The developed simulation model and control algorithm will also be validated on laboratory prototype The simulation results show that compared with the scheme without using midpoint voltage balance and inverter current sharing algorithm, the method used in this report effectively suppresses the imbalance of neutral point potential and the output imbalance of parallel inverters, and improves the grid connection quality of inverter output current.